Agronomic Characterization of Wheat Mutants (Triticum aestivum) of M3 Generation Planted in Sukabumi - Sari, Laela; Purwito, Agus; Sopandie, Didy; Purnamaningsih, Ragapadmi; Sudarmonowati, Enny (Biosaintifika: Journal of Biology & Biology Education, 2016)
The purpose of this study was to identify the selection criteria to obtain a superior mutant derived from the wheat plants of such varieties as Dewata, Selayar and Alibey, adaptive in medium land. The analysis of agronomic growth characters showed a significantly effect on a growth percentage of the initial growth (8 mutants), flowering time (1 mutant), panicle stem length (15 mutants), number of panicles (7 mutants), the number of grains per panicle (8 mutants), grain weight observed (8 mutants), grain weight per genotype (6 mutants), leaf area (2 mutants) and leaf greenness (5 mutants). The effects on the characters of ripe time, harvest, panicle length and plant height were not significant. The mutants of Dewata, Selayar and Alibey could be selected based on the characters of panicle stem length, number of grains per panicle and grain weight per observation because these characters generated more mutants than the other characters. The correlation analysis between the characters of growth and yield components of wheat mutants showed that the number of grains per panicle was positively correlated with the grain weight observed, while the length of panicle stem was positively correlated with grain weight per genotype, number of panicles and leaf area. Hopefully some mutants produced could adapt to the tropical medium land, thus adding to the diversity of wheat germplasm in Indonesia, thereby reducing the import of wheat to Indonesia.How to CiteSari, L., Purwito, A., Sopandie, D., Purnamaningsih, R. & Sudarmonowati, E. (2016). Agronomic Characterization of Wheat Mutants (Triticum aestivum) of M3 Generation Planted in Sukabumi. Biosaintifika: Journal of Biology & Biology Education, 8(3), 353-361.